REPRESENTASI MASYARAKAT INGGRIS ERA VICTORIA DALAM NOVEL “OLIVER TWIST” KARYA CHARLES DICKENS ANALISIS RESEPSI SASTRA HANS ROBERT JAUSS - Nurul Wahidah (Nusantara Hasana Journal, 2022)
A history of reception about literary work is conducted by the differences of reader horizon of expectation. The difference of its results are based on the reader background. A horizon of expectation of a reader can be vary such as education, experience, knowledge, and understanding skill to interpreting a meaning. Beside a difference of a reader horizon, reader can not be also separated from giving meaning to its text. While in literary work has an open place that must be filled by reader. A reader concern giving meaning by doing reading action. In Oliver Twist novel by Charles Dickens depicted all conditions of England in Victorian Period. Reception theory of Hans Robert Jauss the first theses will be used for guidance to this analyze. That theory also used as approach to solve the case in this study. While the writer will apply a qualitative descriptive method base on the act of reading and text analyses. The findings show that the condition of people in Victorian Era face sorrowful and darkness. These situation sharply spread of a poverty, starving, oppression, and injustice. Those all situations are clearly caused by industry revolution. Govermen run an amoral rules which society does not have sympathy, care, and responsibility.